Effect of body composition on fitness performance in young male football players - Huseyin Husrev Turnagol; Süleyman Bulut; Ş. Alpan Cinemre; Muhammed Mustafa Atakan; Evrim Unver; Necip Demırcı (Selcuk University, 2017)
The purpose of this study was to investigate the relationship between anthropometric measurements and athletic performance in young football players. Total seventeen male football players (age: 17.0 years; height: 180.9±5.99 cm and weight; 71.36±6.30 kg) agreed to participate to this study, on voluntary basis. Body composition measurements including body mass, fat mass, bone mineral content, lean mass were made by using Dual-energy X-ray absorptiometry (DXA). In order for the participant to be evaluated athletic performance, countermovement jump (CMJTT), squat jump (SJTT), T-agility test, 30m sprint test and 6 x 40m repeated sprint test were performed respectively. Pearson correlation coefficient (r) was used to relationship between body composition and athletic performance parameters. As a result, negatively significant correlation was found between sprint times and body mass (p lt;0.05). There was also negative correlation between repeated sprint performance (measured in time) and lean Mass (LM), lean mass index (LMI), appendicular LM and appendicular LMI (p lt;0.05). There were also negatively significant correlation among T-agility test, body mass and LM was (p lt;0.05). Non-significant correlation was seen among CMJT, SJT and body mass index and other anthropometric variables. In conclusion, for football players, changes in body composition are of great importance in athletic performance, especially sprint and agility.